Pronunciation Patterns and Challenges of the Japanese Long Vowel (Chouon) /ei/ Among Indonesian Students - Febriyanti, Rike (Universitas Negeri Semarang, 2024)
This study examines the pronunciation patterns of the Japanese vowel sequence /ei/ among 62 students from six universities across six provinces in Indonesia. In Japanese, the vowel sequence /ei/ is commonly neutralized to /e:/. According to Takayama (1992), this neutralization is incomplete in formal or careful speech, where /ei/ is pronounced distinctly as /ei/. Hashimoto (2006) observed that speakers alternate between /ei/ and /e:/, particularly at the ends of sentences. This research explores how Indonesian students, who typically pronounce words according to their written forms, produce the vowel sequence /ei/ in both the initial and final positions of familiar Japanese words. This study was conducted between January to June 2024. Participants were tasked with identifying instances where native Japanese speakers used the long vowel /ei/ in sentences. They then recorded their pronunciations of these words in various positions. The recordings were analyzed using PRAAT software. Results show that native Japanese speakers typically pronounce /ei/ as a long /e:/ with an average duration of 0.173 seconds. In comparison, Indonesian learners pronounced /ei/ in